Residential Property Valuation Using Geographic Information System - Ismail, Suriatini (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1998)
The comparison method has been the most acceptable method of valuation particularly for residential property. The valuation process generally involves two main types of data which can be classified as spatial and textual data. Several manual problems encountered during the valuation process due to the massive amount of data involved. GIS is a viable alternative to deal with the problems because of its capability to deal with both types of data integratedly and efficiently. This paper highlights the main problems of manual process of valuation and outlines a possible application of GIS via the sample session of VALGIS, a GIS-based property valuation package academically developed at Center for Geographic Information and Analysis (CGIA) Malaysia. VALGIS is capable of carrying out residential property valuation process, easy to use and can expedite the work process.